ENVIRONMENTAL EMISSIONS AND LIFE EXPECTANCY NEXUS: FURTHER EVIDENCE FROM NIGERIA - SUNDAY OSAHON IGBINEDION (Annals of the University of Petrosani: Economics)
The paper examined the nexus between environmental emissions and life expectancy using Johansen co-integration and error correction modeling in Nigeria, applying time series data spanning 1990-2016. The finding reveals that environmental emission (proxied by per capita carbon dioxide) is a significant determinant of life expectancy at birth in Nigeria. Also, results reveal that both improved sanitation facilities and public expenditure on health positively and significantly impact on longevity level in Nigeria. Arising from the findings, the study recommends, amongst others, that relevant government policies that could significantly curtail environmental emissions should be strictly enforced and accorded priority in development policy measures. Such efforts should be complemented by embarking on mass sensitization of the Nigerian populace on the strategies to help keep their environment clean in order to reduce mortality relating to unkempt environment and to improve the health status of the citizens.